Hubungan Penerapan Prinsip Etik Keperawatan dengan Kualitas Pelayanan Keperawatan di Ruang Rawat Inap Rumah Sakit Bhakti Timah Karimun - Muhammad Firdaus; Utari Christya Wardhani; Sri Muharni (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Nursing as a profession, is limited by self-regulation in the form of a code of ethics of killing. The code of ethics of extermination is the basic reference for nurses in carrying out their profession, both in relation to the use of extermination technology and knowledge. The purpose of this study was to determine the relationship between the principle of protection ethics and the quality of service in the inpatient room of Bakti Tin Karimun Hospital. The design of this study was cross-sectional with a sample size of 84 respondents, namely patients in the inpatient room using a purposive sampling technique. Data were collected using a prevention ethics questionnaire to measure the application of the principle of prevention ethics and a prevention service questionnaire to measure the quality of service. Data were analyzed through a chi-square statistical test P Value of 0.007 <0.05, which means that there is a significant relationship between the application of the principle of protection ethics and the quality of protection services in the inpatient room of Bakti Tin Karimun Hospital. So the more optimal the application of protection ethics, the better the quality of protection services. Nurses are expected to be able to apply the principle of optimal care ethics in providing care to patients so that the quality of service in inpatient care is good.